Practically simple reactions convert hydrocarbons to precious chemicals. (15th November 2018) - Morken, James P.
Operationally simple chemistry enables aliphatic carbon–carbon bonds — the 'girders' in the framework of many organic molecules — to be prepared from widely available hydrocarbons known as alkenes. Cross-coupling reactions for making aliphatic carbon–carbon bonds.